Comparison of Efficacy of Nebulisation with Salbutamol versus Adrenaline in Acute Bronchiolitis in Children aged Two Months to Two Years - Sah, Vijay Kumar; Giri, Arun; Sah, Sanjay; Niraula, Niraj (Journal of Nobel Medical College, 2019)
Background: Bronchiolitis is an acute, highly communicable lower respiratory tract infection. A variety of agents ranging from nebulised racemic epinephrine, salbutamol and routinely available levoepinephrine have been tried. The Present study was aimed at comparing the effectiveness of adrenaline and salbutamol in acute bronchiolitis in children aged 2 months to 2 years. Materials and Methods: The Present study was conducted at Nobel medical College Teaching Hospital over the period of one year from Feb 2018 to Jan 2019. Two different cohorts were identified in which clinically diagnosed cases and were grouped into Group A and Group B to receive the different drugs as per the study protocol. Respiratory Distress Assessment Instrument (RDAI) Scores was used for clinical assessment. Results: The age of the patients ranged from 2 months to 24 months with a median of 8 months. The males constituting about 57.42% of the study population of 155 patients. On comparing the prenebulisation variables with 10 and 30 minutes post nebulisation values, it was found that Both adrenaline and salbutamol caused overall significant improvement in RR (p-value <0.00001 in both groups) except in the age group of 19-24 months. Adrenaline was seen to be superior to salbutamol in decreasing the RR (p<0.0001) except for children in the age group of 19-24months. Adrenaline also caused greater rise in heart rate in comparison to salbutamol in all age groups. Conclusion: This study concludes that Adrenaline was seen to be superior to salbutamol in decreasing the RR and RDAI, although it showed variance with age.